2015
DOI: 10.1371/journal.pone.0130021
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategy for Hepatocellular Carcinoma Patients with Portal/Hepatic Vein Tumor Thrombosis

Abstract: BackgroundPortal/hepatic vein tumor thrombosis (PVTT/HVTT) in hepatocellular carcinoma (HCC) is a sign of advanced stage disease and is associated with poor prognosis. This study investigated the surgical outcomes of patients with HCC and PVTT/HVTT to determine the most appropriate surgical treatment strategy for these patients.Materials and MethodsThe study population included 77 HCC patients from January 2004 to June 2009 who underwent hepatectomy in our department and were diagnosed with PVTT/HVTT based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 45 publications
(51 reference statements)
1
44
0
Order By: Relevance
“…For HCC patients with PVTT, anatomical resection showed no advantage compared with non-anatomical resection regarding postoperative outcomes in our study, consistent with previous studies [31, 32]. The resection margin has also been evaluated as a prognostic factor for long-term outcomes after HCC resection; however, the significance of this variable also remains controversial [19, 32, 33]. Our previous study explored patterns of intrahepatic micrometastasis using large pathological sections of liver resection specimens from 113 patients with solitary HCC [34].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For HCC patients with PVTT, anatomical resection showed no advantage compared with non-anatomical resection regarding postoperative outcomes in our study, consistent with previous studies [31, 32]. The resection margin has also been evaluated as a prognostic factor for long-term outcomes after HCC resection; however, the significance of this variable also remains controversial [19, 32, 33]. Our previous study explored patterns of intrahepatic micrometastasis using large pathological sections of liver resection specimens from 113 patients with solitary HCC [34].…”
Section: Discussionsupporting
confidence: 89%
“…These findings suggest that en bloc resection may be superior to peeling off resection as an operative procedure for HCC patients with PVTT. Although three previous studies have compared the survival outcomes between en bloc and peeling off resections for HCC with PVTT, to our knowledge, our study comprises the largest study population and presents the longest follow-up data reported to date [1719]. In addition, the current findings, which were obtained after balancing patient demographics, liver function reserves, and tumor characteristics between the en bloc and peeling off groups, provide important data that may be used to establish an optimal surgical strategy for the management of HCC patients with PVTT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that hepatic resection for MVI may be advantageous in terms of avoiding liver failure secondary to tumor thrombus (13)(14)(15)(16)(17). However, the indications for hepatic resection and transarterial therapy in HCC cases with MVI differ among institutions (2,3,12,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…According to the American Association for the Study of the Liver Disease/Barcelona Clinic for Liver Cancer Staging System and treatment guidelines, the only proposed treatment option for HCC patients with PVTT is sorafenib chemotherapy[4]. In Asia, various treatments including hepatectomy and transcatheter arterial chemoembolization (TACE) have been attempted and possible prolongation of overall survival (OS) has been repeatedly reported[5]. We herein report the first case of a patient with an initially unresectable advanced HCC with PVTT who underwent curative hepatectomy after sorafenib and TACE, showing complete histological response.…”
Section: Introductionmentioning
confidence: 99%